The Effect Of Internal Audit And External Audit On Accounting Fraud In View From The Fraud Triangle Theory (Study Of Soe Companies In Medan City) - Hasibuan, Muhammad Rezki Ripaldo; Siregar, Saparuddin; Harahap, Muhammad Ikhsan (Universitas Dehasen Bengkulu, 2023)
This study aims to determine the effect of internal audit and external audit on accounting fraud/fraud in terms of the fraud triangle theory (study of state-owned companies in Medan). This research uses quantitative methods, primary data collection techniques by distributing questionnaires. The population and sample are 45 respondents and use a saturated total sampling technique. This study uses the SPSS statistical tool. Data were analyzed using multiple regression analysis method. The results of this study indicate that Internal Audit has a positive and significant effect on Accounting Fraud. This is evidenced by because the tcount for the Internal Audit variable (3.088) is greater than the ttable (2.018) and the sig value is 0.004 <0.05. External Audit has a positive and significant effect on Accounting Fraud. This is evidenced by because the tcount for the External Audit variable (2.557) is greater than ttable (2.018) and the sig value is 0.014 <0.05. As well as the F test shows that Internal Audit and External Audit have a simultaneous and significant positive effect on Accounting Fraud. This is evidenced by the Fcount value of (7.765) greater than Ftable (3.22) and a sig value of 0.001 <0.05. Meanwhile, the Adjusted R Square value is 0.235. This shows that the independent variables, namely Internal Audit and External Audit, are able to explain the dependent variable, namely Accounting Fraud of 23.5%, the remaining 76.5% is explained by other variables outside the regression model.